Synthesis And Characterization Of Wox Zno Nanocomposites On Polyethylene Terephthalate (Pet) Fiber For Photocatalytic Application - Myo, Thuya Thein (2016)
The drawback of using ZnO semiconductor photocatalyst to treat synthetic dyes is its poor photocatalytic activity. This is attributed to its rapid recombination of charge carriers, and loses of particles by flowing water during photodegradation process. In this research, ZnO rods were synthesized by solution precipitation method. By studying synthesis parameters such as capping agent (PVP), growth duration and growth temperature, ZnO rods with the best photocatalytic performance in removal of RhB dye under UV irradiation were synthesized using PVP at growth duration of 30 min and growth temperature of 90 oC. These ZnO rods achieved photodegradation efficiency of 98.8 % and rate constant of 0.058 min‒1 after 75 min UV irradiation, respectively. It is noted that although ZnO nanodisks offered a larger (002) polar surface, their photodegradation efficiency was poor as compared to ZnO rods. Refined growth mechanisms of stacked ZnO rods and ZnO nanodisks are proposed based on the zeta potential analysis. In order to improve the photocatalytic performance, Ni particles were deposited onto the ZnO rods using solution precipitation method, followed by calcination and reduction in H2 atmosphere at 500 oC for 2 h. The deposition of Ni particles on the surface of ZnO rods was confirmed by the results of field emission scanning electron microscope (FESEM), energy dispersive X-ray spectroscopy (EDX), transmission electron microscope (TEM), room temperature photoluminescence (RTPL) and X-ray photoelectron spectroscopy (XPS). The Ni/ZnO nanocomposites experienced surface plasmon resonance (SPR) effect in RTPL measurement with a RUV/Vis ratio up to 40.6. However, this unique optical property did not favor for the photocatalytic performance of ZnO rods. The Ni particles introduced defects (recombination centers) which deteriorated the photocatalytic activity of Ni/ZnO nanocomposites. The best Ni/ZnO nanocomposites, with photodegradation efficiency of 61.7 % and rate constant of 0.033 min‒1 (after 30 min UV irradiation), were produced under calcination temperature of 500 oC and 0.03 M of nickel nitrate solution concentration. The WOx/ZnO nanocomposites were synthesized using solution precipitation method too. The WOx particles consisted of a mixture of WO2 and WO3 as proven by XPS analysis. Generally, >90 % photodegradation efficiency of RhB dye removal could achieved at 30 min by these WOx/ZnO nanocomposites as compared only 74.4 % by ZnO rods. In order to minimize the lost of particles in water system, WOx/ZnO nanocomposites were grown on PET fibers. This was achieved by depositing WOx particles on the ZnO rods pre-grown on the PET fibers. The optimized photocatalytic performance (RhB solution under stagnant condition, UV irradiation) was achieved for WOx/ZnO nanocomposites prepared at 0.01 M sodium tungstate solution in which the photodegradation efficiency and rate constant are 89.5 % and 0.030 min‒1, respectively. The WOx particles/ZnO nanocomposites under circulated RhB solution still maintained good coverage on PET fiber with consistent photocatalytic performance (rate constant of 0.0073 min‒1) even after 15 h.